2023
DOI: 10.26599/jac.2023.9220665
|View full text |Cite
|
Sign up to set email alerts
|

Low thermal conductivity of dense (TiZrHfVNbTa)Cxhigh-entropy carbides by tailoring carbon stoichiometry

Abstract: Transition metal carbides are promising candidates for thermal protection materials due to their high melting points and excellent mechanical properties. However, the relatively high thermal conductivity is still a major obstacle to its application in an ultra-high-temperature insulation system. In this work, the low thermal conductivity of dense (TiZrHfVNbTa)C x (x = 0.6-1) high-entropy carbides has been realized by adjusting the carbon stoichiometry. The thermal conductivity gradually decreases from 10.6 W•m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…High‐entropy carbides are the solid solutions of monocarbides, composed of five or more metal elements in roughly equal equimolar proportions and inherit the properties of the related monocarbides, which shows high thermal stability and high hardness 7–27 . High‐entropy carbides also have the feature of forming nonstoichiometric composition 16–23 . However, carbon vacancies, acting as structural defects in the monocarbides and high‐entropy carbides, may play different roles in the two materials due to the high‐entropy effect and severe lattice distortion present in the latter one.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High‐entropy carbides are the solid solutions of monocarbides, composed of five or more metal elements in roughly equal equimolar proportions and inherit the properties of the related monocarbides, which shows high thermal stability and high hardness 7–27 . High‐entropy carbides also have the feature of forming nonstoichiometric composition 16–23 . However, carbon vacancies, acting as structural defects in the monocarbides and high‐entropy carbides, may play different roles in the two materials due to the high‐entropy effect and severe lattice distortion present in the latter one.…”
Section: Introductionmentioning
confidence: 99%
“…High-entropy carbides also have the feature of forming nonstoichiometric composition. [16][17][18][19][20][21][22][23] However, carbon vacancies, acting as structural defects in the monocarbides and high-entropy carbides, may play different roles in the two materials due to the high-entropy effect and severe lattice distortion present in the latter one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that the added Si with a low melting point and the formed carbon vacancy could obviously decrease the densification temperature from 1900 to 2000°C for stoichiometric high-entropy carbides to 1600°C for the non-stoichiometric ones. Very recently, Chen et al [14] and Zhang et al [30] prepared non-stoichiometric high-entropy carbide ceramics by carbothermal reduction reaction followed by pressureless sintering and found that the thermal conductivity decreased with the increased content of carbon vacancy.…”
Section: Introductionmentioning
confidence: 99%
“…The two sublattices not only affect the calculation of the configurational entropy but also influence the diffusion-related behaviour of each other. Especially for the high-entropy transition metal carbides, the generally existing non-stoichiometry in the carbon site of the monocarbides will result in a similar nonstoichiometry in the high-entropy carbides [12][13][14][15][16]. For instance, zirconium carbide (ZrC) has a broad non-stoichiometry ranging from 0.49 to 1 [17].…”
Section: Introductionmentioning
confidence: 99%